The Effect of Good Corporate Governance, Dividend Policy, and Capital Structure on Company Value: Empirical Study of Property and Real Estate Companies Listed on the Indonesian Stock Exchange for the 2016-2021 Period - Wulandari, Septi Dwi; Arini, Lusia Sri (Journal of Social Research, 2023)
This research aims to determine the effect of Good Corporate Governance, Dividend Policy, and Capital Structure on Firm Value. The object of this research is to property and real estate companies listed on the Indonesia Stock Exchange from 2016-2021. This research was conducted on 13 property and real estate companies by predetermined criteria. This study uses statistical analysis in the form of a multiple linear regression test. The sampling technique used is purposive sampling using SPSS 25 software. Based on The results of this study indicate that Managerial Ownership has a positive and not significant effect on Firm Value. Institutional Ownership has a negative and significant effect on Firm Value. Independent Commissioner has a negative and significant effect on Firm Value. Dividend Policy has a positive and significant effect on Firm Value. Capital Structure has a positive and significant effect on Firm Value.